DAMPAK PENGGUNAAN APLIKASI TIKTOK DIKALANGAN MAHASISWA KOTA BENGKULU MENURUT PANDANGAN MAJELIS ULAMA INDONESIA (MUI) KOTA BENGKULU - Yudha, Ivando; Hasanah , Uswatun; Fitri, Sherly Nelsa (JURNAL RUANG HUKUM, 2023)
This study aims to determine the use of the TikTok application among students in Bengkulu City according to the view of the Majelis Ulama Indonesia (MUI) in Bengkulu City. This study uses empirical legal research to examine the law as a pattern of behavior that applies to the application of legal regulations. The use of the TikTok application among students in Bengkulu City according to the view of Majelis Ulama Indonesia (MUI) in Bengkulu City, is to have positive and negative influences. Positive influences include having many friends and fans, learning new things from preferred accounts, and trying to participate in spreading good things in cyberspace. While the negative impact is shame makes TikTok users sink even more with their fun to rock, A lot of content created by TikTok users does not filter which videos are appropriate or inappropriate to upload and seeing videos uploaded by other users can be a waste of time.